PENGARUH PELAYANAN, FASILITAS DAN DAYA TARIK WISATA TERHADAP KEPUTUSAN BERKUNJUNG (STUDI PADA PENGUNJUNG OBJEK WISATA SA’PAK BAYO BAYO) - Mey Enggane Limbongan (JSSHA ADPERTISI JOURNAL, 2022)
This study aims to find out the effect of service, facility and tourist attraction on visit decision to visit Sa’pak Bayo Bayo Tourism Object in Sangalla, Tana Toraja. The result of t-test show that service variable does not have a significant effect on decision to visiting the tourism object. Otherwise, facilities and tourist attraction variables partially had a positive and significant effect on visit decision. The result of F-test show that all the independent variable simultaneously have a positive and significant effect on visit decision. The results of this study can be used by tourism object managers in developing and improving the quality of tourist objects in terms of services, facilities and tourist attractions.